Design and Study of Novel Tunable ELF-PEMF System for Therapeutic Applications. Issue 4 (4th July 2022) - Kohli, Himani; Srivastava, Sangeeta; Oza, Manan; Chouhan, Satish; Verma, Shivani; Bansal, Anju; Kumar, Bhuvnesh; Sharma, Sanjeev Kumar
ABSTRACT: Microbial infection is a major barrier to wound care and repair process of the cells. Various US-FDA-approved drugs and surgical procedures have been used for wound healing progression. However, the use of these pharmaceutical products has an associated toxicity and may produce harmful side effects. To overcome these problems, researchers worldwide are trying to develop non-invasive wound healing processes for wound care. We have developed a unique, tunable and Arduino microcontroller-based extremely low-frequency (ELF) pulsed electromagnetic field (PEMF) device for accelerating the wound healing process by reducing the microbial infection. The layout and detailed design of the device are presented here. Simulations carried out for the fabrication of the Helmholtz coil used in the PEMF device are also presented. This system can provide the flexibility of dose substance by selecting the type and frequency of the waveform, exposure duration, and magnetic field strength. To test the efficacy of the device in the biological system, we have designed colony-forming unit assay in Staphylococcus aureus with an exposure to PEMF in the frequency range of 5–30 Hz for 90 min. The experiments have been conducted in controlled EMF environments as per the international standard exposure guidelines. The results show a 60% reduction in S. aureus CFU after 90 minutes of PEMF exposure, and hence, show that the designed system is very effective for wound care by reducing the microbial growth.